The West Indian generation : remaking British culture in London, 1945-1965 - Bidnall, Amanda (Migrations and identities., 2017)
The West Indian Generation: Remaking British Culture in London, 1945-1965 shows the progressive potential - and stultifying limits - of cultural collaboration between West Indian artists and entertainers who settled in London and the city's engines of mainstream culture.